The Effect of Financial Performance and Corporate Social Responsibility on Firm Value with Firm Size as a Control Variable - Umboh, Olivia Mariska; Yanti, Harti Budi (Transpublika Publisher, 2025)
The main objective of this research is to explore how financial performance and corporate social responsibility influence the value of companies in the consumer goods industry in Indonesia, using firm size as a factor to consider. The study will concentrate on companies listed on the Indonesia Stock Exchange from 2021 to 2023. The research will gather data from previous studies and select samples based on specific criteria. A total of 285 samples will be analysed in this study. The data will be analysed using panel data regression analysis, which is suitable for examining how the variables interact with each other over the designated time period. The results of this research indicate that companies with higher profitability, as measured by Return on Assets (ROA), tend to have a greater firm value. Conversely, there was no notable impact on firm value from Corporate Social Responsibility (CSR), implying that consumers and investors may not rate CSR initiatives highly when evaluating company worth. Furthermore, the variable of firm size was shown to have a significant influence on firm value, with larger companies usually having a higher firm value.